Remuneration of bank managers – problems and potential solutions - Marcinkowska, Monika (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
The issue of the remuneration of bank managers is indicated as one of the fundamental problems of corporate governance and is pointed out as one of irregularities that led to the financial crisis. Based on the literature review, the paper summarizes the identified inadequacies of management compensation systems in banks: overcompensation, short-termism and the related incentive for excessive risk-taking, manipulation by managers, poor disclosure and the lack of proper oversight from the supervisory boards. Another problem is that – although as a rule the management compensation system should be used as a tool to motivate managers (agents) to act in a way to achieve the objectives of the owners (and other legitimate stakeholders) – the literature shows the unequivocal results of the pay-performance research. As the described problems in the banking industry have grown enormously, the recommendations and regulations concerning the management remuneration policies and practices are being enacted. The paper shows however that their implementation raises many problems and challenges. Therefore there is a need to further analyze the issue of designing a proper bank managers’ compensation model. The postulates concerning performance evaluation process, linkage with risk, instruments and disclosure are presented
Argumenta Oeconomica, 2014, Nr 1 (32), s. 41-74
Keywords: management compensation; corporate governance in banks